Criminal Law Sanctions for Illegal Logging of Forests Carried Out by Corporations Based on Law of the Republic of Indonesia Number 18 of 2013 concerning Prevention and Eradication of Forest Damage - Ismaidar Ismaidar; T. Riza Zarzani; Arnovan Pratama Surbakti (International Journal of Sociology and Law, 2024)
Forest areas are open natural resources that have potential and an important role in supporting human needs. However, as time goes by, natural resources in the forestry sector are starting to decline due to the large number of business entities or corporations carrying out illegal logging activities. If this is allowed to continue continuously, damage to Indonesia's forests will increase and will have a major impact on the economy due to decreased state income. The research method used in this research is a normative legal method which examines Law Number 18 of 2013 concerning Prevention and Eradication of Forest Destruction and other laws as research material by taking a statutory approach (Statute Approach) obtained from literature studies ( Library Research). This research aims to determine the impact of illegal logging carried out by corporations and to determine criminal legal sanctions for illegal logging carried out by corporations based on Law number 18 of 2013 concerning Prevention and Eradication of Forest Damage. From the problem formulations above, it can be concluded that corporate crime resulting from illegal logging activities is a major crime and is very dangerous and threatens the lives of humans, animals and plants.